2018
DOI: 10.1002/adfm.201800793
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Layered Organogel–Hydrogel Hybrids with Controllable Wetting and Swelling Performance

Abstract: Soft gels that integrate the water retention of hydrogels and the water swelling resistance of organogels are sought by researchers. Such materials have useful properties and potential applications in stretchable and biointegrated fields, such as tissue engineering, microfluidics, and biomedical devices. This study reports a simple yet versatile method for assembling hydrogels and organogels into covalently tethered hybrids to provide robust properties, such as excellent stretchability, tough interfacial bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 45 publications
0
63
0
Order By: Relevance
“…In recent years, remarkable progress has been achieved in the development of hydrogel‐hybrid system and hydrogel‐interface chemistries based on diverse adhesion mechanism, such as acylhydrazone bonding, [ 28 ] nanoparticles modification, [ 29 ] double bonds modification and copolymerization, [ 30 ] and the hydrogen‐bonding mechanism, [ 31 ] which exhibit great promising for developing unique smart soft materials. The interfacial adhesion modification through hydrogel‐interface chemistries between the dielectric organogel layer and ionic hydrogel conductors can significantly enhance the stability and practicality of the whole device of capacitive strain sensor.…”
Section: Formulation and Characterization Of Dynamically Super‐tough Hydro/organo‐gelsmentioning
confidence: 99%
“…In recent years, remarkable progress has been achieved in the development of hydrogel‐hybrid system and hydrogel‐interface chemistries based on diverse adhesion mechanism, such as acylhydrazone bonding, [ 28 ] nanoparticles modification, [ 29 ] double bonds modification and copolymerization, [ 30 ] and the hydrogen‐bonding mechanism, [ 31 ] which exhibit great promising for developing unique smart soft materials. The interfacial adhesion modification through hydrogel‐interface chemistries between the dielectric organogel layer and ionic hydrogel conductors can significantly enhance the stability and practicality of the whole device of capacitive strain sensor.…”
Section: Formulation and Characterization Of Dynamically Super‐tough Hydro/organo‐gelsmentioning
confidence: 99%
“…For instance, Asatekin's work [246] demonstrated a new, simple, and reproducible method called interfacially initiated free-radical polymerization (IIFRP) for fabricating membranes with ultrathin (<100 nm), defect-free hydrogel selective layers on porous supports. In the research by Liu et al, [247] they reported a simple yet versatile method for assembling macroscopic-layered organogelhydrogel hybrids via UV initiated free-radical polymerization to provide robust properties, such as excellent stretchability, tough interfacial bonds, enduring anti-swelling, and low dehydration.…”
Section: Via Monomersmentioning
confidence: 99%
“…and function for each layer can be particularly important in diverse applications. [247,[386][387][388][389][390] Figure 8. Illustrations of core-shell-structured hydrogels.…”
Section: Multi-layered Hydrogelsmentioning
confidence: 99%
“…On the basis of aforementioned developments, complex configurations can be obtained by integrating separate units with specific heterogeneous structure and distinct deformation modes. [ 15,25,26 ] These composite hydrogels usually have a continuous surface despite of different localized curvatures. The geometric continuity results in relatively limited displacement between the neighboring regions, and thus the small amplitude of deformation.…”
Section: Figurementioning
confidence: 99%